1995
DOI: 10.1136/jnnp.58.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolism of cerebral glucose after stereotactic leukotomy for refractory obsessive-compulsive disorder: a case report.

Abstract: Brain glucose metabolism was investigated with PET and ['8F]fluorodeoxyglucose, before and after a bifrontal stereotactic leukotomy in a 37 year old woman with refractory obsessive-compulsive disorder. A bilateral decrease in glucose metabolism was found in the orbital frontal cortex after psychosurgery. Glucose metabolism was decreased to a lesser degree in Brodmann's area 25, in the thalamus, and in the caudate nucleus. Clinical improvement in obsessive-compulsive disorder after stereotactic tractotomy seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…36,37 Taken together, the results of these studies suggest that reduction of thalamic activity, and a resultant decrease in thalamocortical excitation, 18 may represent a final common pathway to response to a variety of different treatments in nondepressed OCD patients. 19,38 As in many prior studies, 5,[8][9][10]12,17,36 the magnitude of change in thalamic metabolism did not correlate with the degree of response of OCD symptoms to intensive CBT. This suggests that while decreasing thalamic activity may be a marker of response to treatment in OCD it is not specifically related to the extent of symptom improvement.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…36,37 Taken together, the results of these studies suggest that reduction of thalamic activity, and a resultant decrease in thalamocortical excitation, 18 may represent a final common pathway to response to a variety of different treatments in nondepressed OCD patients. 19,38 As in many prior studies, 5,[8][9][10]12,17,36 the magnitude of change in thalamic metabolism did not correlate with the degree of response of OCD symptoms to intensive CBT. This suggests that while decreasing thalamic activity may be a marker of response to treatment in OCD it is not specifically related to the extent of symptom improvement.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, decreasing cingulate activity may sometimes be associated with improvement in OCD symptoms but does not appear to be a necessary mechanism of action for treatment response. Instead, the functional changes most strongly associated with treatment response in OCD are decreases in activity in the right OFC, 8,[10][11][12][13]36,37,42,43 right caudate 9,11,12,14,16,17,36,37,42 and thalamus. 9,11,15,36,37 In contrast to the effects of pharmacotherapy on brain function, enhancement of dACC activity may be a primary mechanism of action of CBT for OCD.…”
Section: Discussionmentioning
confidence: 99%
“…This result corresponds well with previous PET studies of patients at rest in which orbitofrontal hypermetabolism was identified as a potential biomarker of OCD severity, based on similar linear correlations with clinical measures and its normalization of activity posttreatment. [12][13][14][67][68][69] Correlations of this kind have also been reported in symptom provocation studies, in this case related to orbitofrontal hyperactivation above baselines states. 17,20,25 Most recently, orbitofrontal dysfunction was identified in firstdegree relatives of patients with OCD, providing strong evidence that it may be a specific vulnerability marker (endophenotype) of illness.…”
Section: Commentmentioning
confidence: 77%
“…Furthermore, the severity of OC symptoms has been reported to correlate with the degree of increased orbitofrontal (OF) activity (Busatto et al, 2000;McGuire et al, 1994;Swedo et al, 1989); while normalization of OF activity (and in some studies caudate activity) has been observed with successful pharmacologic, surgical (stereotactic leukotomy), or behavioral treatment (Baxter et al, 1992;Biver et al, 1995;Molina et al, 1995;Saxena et al, 2001;Schwartz et al, 1996). Interestingly, scripted obsessional content, employed as provocative stimuli, increased orbitofrontal blood flow in normal controls as well as patients with OCD (Cottraux et al, 1996;Maitaix-Cols et al, 2003).…”
Section: Obsessive-compulsive Disordermentioning
confidence: 90%